Construction of Genetic Linkage Maps Using SSR Markers and Identification of Flower Bud-Related QTLs in Nightlily (Hemerocallis citrina) - Feifan Hou; Xufei Liang; Rui Chen; Xuan Ji; Hongtao Li; Mengyue Jing; Yang Gao; Yuting Liu; Sen Li; Guoming Xing; Yanfang Wang (Agronomy)
Nightlily (Hemerocallis citrina Baroni) is an important vegetable with edible floral organs. It possesses considerable economic value due to its edibility, ornamental, and medicinal properties. However, the genetic linkage map construction and quantitative trait locus (QTL) mapping of nightlily have not been performed. This study used two varieties ‘Dongzhuanghuanghua’ and ‘Chonglihua’ of nightlily as cross parents to establish an intraspecific hybridization population of 120 F1 progenies. The ‘Datonghuanghua’ (female) variety of nightlily and ‘Lullaby Baby’ (male) variety of daylily were selected to construct an interspecific hybridization population of 55 F1 progenies. A total of 965 expressed sequence tag–simple sequence repeats (EST-SSRs), along with 20 SSR markers from various sources, were used for genetic mapping. Among these markers, CT/TC (9.24%) of the dinucleotide and GGA/GAG/AGG (4.67%) of the trinucleotide repeat motifs were most abundant. In the intraspecific hybridization genetic map, a total of 124 markers were resolved into 11 linkage groups, with a total map length of 1535.07 cM and an average interval of 12.38 cM. Similarly, the interspecific hybridization map contained 11 linkage groups but with 164 markers, a total map length of 2517.06 cM, and an average interval of 15.35 cM. The two constructed maps had 48 identical markers and demonstrated good collinearity. The collinearity analysis showed that 161 markers hit the genomic sequence of the published H. citrina genome, indicating that the two constructed genetic maps had high accuracy. Phenotypic data were investigated over two consecutive years (2018 and 2019) for flower bud fresh weight, dry weight, and bud length in two hybridization populations. A total of nine QTLs associated with flower bud-related traits were identified, among which those located on linkage group 8 of the intraspecific genetic map and linkage group 4 of the interspecific genetic map showed good stability. All nine QTLs had LOD values of not less than 4 and PVE values of not less than 15% over two years. This is the first report about the intra- and interspecific genetic map construction and QTL mapping of the flower bud-related traits in nightlily based on a genetic map. The results promote marker-assisted breeding and offer insights into the mechanisms underlying important traits of the genus Hemerocallis.